2018
DOI: 10.3389/fmicb.2018.00239
|View full text |Cite
|
Sign up to set email alerts
|

A Damaged Oxidative Phosphorylation Mechanism Is Involved in the Antifungal Activity of Citral against Penicillium digitatum

Abstract: Citral exhibits strong antifungal activity against Penicillium digitatum. In this study, 41 over-expressed and 84 repressed proteins in P. digitatum after 1.0 µL/mL of citral exposure for 30 min were identified by the iTRAQ technique. The proteins were closely related with oxidative phosphorylation, the TCA cycle and RNA transport. The mitochondrial complex I, complex II, complex III, complex IV and complex V, which are involved in oxidative phosphorylation were drastically affected. Among of them, the activit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
44
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(52 citation statements)
references
References 53 publications
8
44
0
Order By: Relevance
“…Our previous study demonstrated that the generation of reactive oxygen species (ROS) is one of the major proposed mechanisms of EPI-induced liver injury, which leads to cell membrane damage and results in the release of marker enzymes of hepatotoxicity. Under the condition of oxidative stress, the tricarboxylic acid (TCA) cycle is slowed down, resulting in decreased production of ROS (13,14). The two crucial energy supply substances for the mitochondrial TCA cycle, succinic acid and malic acid are increased due to the dysfunction of mitochondria (15).…”
Section: Discussionmentioning
confidence: 99%
“…Our previous study demonstrated that the generation of reactive oxygen species (ROS) is one of the major proposed mechanisms of EPI-induced liver injury, which leads to cell membrane damage and results in the release of marker enzymes of hepatotoxicity. Under the condition of oxidative stress, the tricarboxylic acid (TCA) cycle is slowed down, resulting in decreased production of ROS (13,14). The two crucial energy supply substances for the mitochondrial TCA cycle, succinic acid and malic acid are increased due to the dysfunction of mitochondria (15).…”
Section: Discussionmentioning
confidence: 99%
“…The membrane permeability of G. citri‐aurantii cells exposed to 0, 1/2 MIC and MIC GA was analysed by measuring the fluorescence values after propidium iodide (PI) staining (OuYang et al ). The 1‐day‐old mycelia were collected from the PDB and resuspended in 100 ml PBS.…”
Section: Methodsmentioning
confidence: 99%
“…and, the antifungal effect of E. globulus EO against Aspergillus flavus and Aspergillus parasiticus , Aspergillus fumigatus and Aspergillus niger . In the literature the citral compound also has been reported for its good antimicrobial activity against Penicillium italicum , Rhizopus stolonifer , P. digitatum , Aspergillus flavus and Aspergillus ochraceus . Zheng et al .…”
Section: Discussionmentioning
confidence: 99%
“…21 and, the antifungal effect of E. globulus EO against Aspergillus flavus and Aspergillus parasiticus, 33 Aspergillus fumigatus and Aspergillus niger. 34 In the literature the citral compound also has been reported for its good antimicrobial activity against Penicillium italicum, Rhizopus stolonifer, 35 P. digitatum, 36,37 Aspergillus flavus and Aspergillus ochraceus. 38 Zheng et al 36 demonstrated that citral can inhibit the growth of phytopathogens, since it can affect the mitochondrial morphology and inhibit the respiratory metabolism, decreasing the activities of tricarboxylic acid cycle related enzymes and change the metabolic pathway.…”
Section: Antifungal Activity Of Eucalyptus Essential Oils In Vitro Testsmentioning
confidence: 99%